Neoadjuvant immunochemotherapy versus neoadjuvant immunoradiotherapy in locally advanced oral squamous cell carcinoma - Ding, Gaofeng; Wang, Wen; Duan, Qingke; Lu, Yufei (Frontiers in Immunology, 2025)
ObjectiveTo juxtapose the efficacy and safety profiles of neoadjuvant immunochemotherapy (NAIC) and neoadjuvant immunoradiotherapy (NAIR) in the management of locally advanced oral squamous cell carcinoma (SCC).MethodsA retrospective analysis of prospectively gathered data was conducted. The study evaluated the impact of NAIC versus NAIR on various parameters, including pathologic complete response (pCR), major pathologic response (mPR), clinical to pathological downstaging, surgical site infection, quality of life, pathologic adverse features, and prognostic outcomes.ResultsThe study encompassed a total of 120 patients, with 73 undergoing NAIC. The pCR and mPR rates in the NAIR group were 25.5% and 63.8%, respectively, closely mirroring the 31.5% and 69.9% observed in the NAIC cohort. A propensity for clinical to pathological downstaging and a reduced incidence of pathologic adverse features was noted in the NAIC population. However, both groups exhibited similar distributions in surgical site infection rates, quality of life metrics, grade 3/4 adverse events, and overall survival. In the Cox proportional hazards model, patients receiving NAIC demonstrated a hazard ratio of 0.87 (95% confidence interval: 0.65-0.98) for 3-year locoregional control, relative to the NAIR group.ConclusionIn the context of locally advanced oral SCC, both NAIC and NAIR exhibited robust efficacy and safety profiles. Nevertheless, NAIC provided superior locoregional control compared to NAIR, thereby emerging as the more favorable initial therapeutic option over NAIR.